Message - Alboghdadly, Dr. Amany Mohamed (Universal Journal of Pharmaceutical Research, 2021)
I am delighted to offer my sincere congratulations to the whole team and members of the Universal Journal of Pharmaceutical Research (UJPR) on their continued success in the scientific publishing process. This journal publishes original research work that contributes significantly to strengthen the scientific knowledge in multidisciplinary areas in pharmacy and pharmaceutical sciences, such aspharmacology, pharmaceutical chemistry, pharmacognosy, pharmacokinetics and pharmacodynamics of the drugs, general medicine, public health, pharmaceuticalmarketing, pharmaceutical microbiology, pharmaceutical biochemistry, pharmaceutical education, and hospital pharmacy, clinical trials and other medical practiceto increase the impact factor of the journal. The editorial members who originate from different countries work hard to improve papers’ quality and increase the publication frequency. The UJPR managing members are very cooperative, supportive, and responding promptly.The major goal of the UJPR is continual improvement and development in order to meet the highest academic publication requirements, strengthen the reviewer database, and inspire future researchers to contribute to the journal by encouraging the publication of high-quality scientific papers. The growing up of UJPR is extremely high in a short period; therefore, I expect more success for our journal to be indexed in famous indexing such as Scopus and Thomson Reuters. I welcome my colleagues to submit their manuscripts for publication considerations forforthcoming issues of UJPR. Finally, I would like to thank all the editorial team members, reviewers, and authors for their support and cooperation. This ranges from the persons who have helped with guidelines, proofreading, and web organizing.